(untitled) (CIPEEX, 2025)
This paper examines the exclusion of evidence obtained by extracting data and private conversations from e-mail and social-network platforms (e.g., WhatsApp and Facebook) without a court order, and the downstream impact on derivative evidence. The introduction grounds the analysis in fundamental rights to privacy and to confidential communications (Federal Constitution, art. 5, X and XII) and in Brazil’s data-protection framework (LGPD), which bar warrantless access to private content. The aim is to set criteria for the (in)admissibility of digital evidence and for derivative contamination, while identifying narrow distinctions developed in case law. The method is a doctrinal and case-law review highlighting Superior Court of Justice rulings on unlawful access to WhatsApp chats, on WhatsApp Web mirroring, and on the application of the fruit-of-the-poisonous-tree doctrine to subsequent evidence. The findings show a baseline exclusionary rule for illegally obtained evidence and its fruits, subject to limited, context-driven distinctions—such as messages sent to corporate e-mail used as a work tool. The case law also equates messaging apps and social networks with traditional correspondence, reinforcing the need for a judicial warrant to access private content. The conclusion is that judicial authorization and data-integrity safeguards are prerequisites for valid digital evidence, and that the fruit-of-the-poisonous-tree doctrine protects fundamental rights and procedural integrity.